Revalidation of Vareuptychia Forster, 1964, description of Vanima gen. nov., and notes on Euptychia cleophes Godman & Salvin, 1889 (Lepidoptera: Nymphalidae: Satyrinae) - Zacca, Thamara; Casagrande, Mirna M.; Mielke, Olaf H. H.; Huertas, Blanca; Espeland, Marianne; Freitas, André V. L.; Willmott, Keith R.; Nakahara, Shinichi; Lamas, Gerardo (Zootaxa, 2020)
Vareuptychia Forster, 1964 stat. rest. is revalidated and comprises two species, V. similis (Butler, 1867) comb. rest. and V. themis (Butler, 1867) comb. nov. Vanima Zacca, Casagrande & Mielke gen. nov. is described to contain Euptychia labe Butler, 1870 (the type species), E. palladia Butler, 1867 and E. lesbia Staudinger, [1886]. The taxonomy of these two genera was initially revised based on morphological and distributional data, and subsequently tested and supported with a Maximum Likelihood analysis using four genes (COI, GAPDH, RpS5 and EF1-a). Lectotypes are designated for Euptychia similis Butler, 1867, E. themis Butler, 1867, E. undina Butler, 1870 and E. lesbia Staudinger, [1886]. No DNA sequences were obtained for Euptychia cleophes Godman & Salvin, 1889 but its transfer to Megisto Hübner, [1819] is supported by morphological evidence. For all taxa treated in this study, a taxonomic catalog, diagnosis, (re)description and illustrations of adults, venation and genitalia are provided, as well as comments on intraspecific variation, sexual dichromatism, ecology and distribution maps.